Cross-modal associations between materic painting and classical Spanish music - Albertazzi, Liliana; Canal, Luisa; Micciolo, Rocco (Frontiers in Psychology, 2015)
The study analyses the existence of cross-modal associations in the general population between a series of paintings and a series of clips of classical (guitar) music. Because of the complexity of the stimuli, the study differs from previous analyses conducted on the association between visual and acoustic stimuli, which predominantly analysed single tones and colours by means of psychophysical methods and forced choice responses. More recently, the relation between music and shape has been analyzed in terms of music visualization, or relatively to the role played by emotion in the association, and free response paradigms have also been accepted. In our study, in order to investigate what attributes may be responsible for the phenomenon of the association between visual and acoustic stimuli, the clip/painting association was tested in two experiments: the first used the semantic differential on a unidimensional rating scale of adjectives; the second employed a specific methodology based on subjective perceptual judgments in first person account. Because of the complexity of the stimuli, it was decided to have the maximum possible uniformity of style, composition and musical colour. The results show that multisensory features expressed by adjectives such as ‘quick’, ‘agitated’, and ‘strong’, and their antonyms ‘slow’, ‘calm’, and ‘weak’ characterized both the visual and acoustic stimuli, and that they may have had a role in the associations. The results also suggest that the main perceptual features responsible for the clip/painting associations were hue, lightness, timbre, and musical tempo. Contrary to what was expected, the musical mode usually related to feelings of happiness or to feelings of sadness and spatial orientation did not play a significant role in the association. The main result of the study consists in showing the existence of cross-modal associations between high complex stimuli.